Non-nutritional factors of milk urea concentration in Holstein cows from large dairy farms in Croatia - Miljenko Konjačić; Nikolina Kelava; Zdenko Ivkić; Ante Ivanković; Zvonimir Prpić; Ivan Vnučec; Jelena Ramljak; Pero Mijić (Mljekarstvo)
Milk urea nitrogen concentration is a reliable indicator of protein energy balance in dairy cows. Concentration of milk urea nitrogen is mostly affected by nutritional factors, but also its concentration can be influenced by some non-nutritional factors. The aim of this research was to determine the effect of season, parity and stage of lactation on concentration of milk urea nitrogen, as well as its association with daily milk yield, milk fat and protein content and somatic cell count. For that purpose, milk control data were collected for 5061 Holstein dairy cows from four dairy farms during five-year period (between January 1999 and December 2005). When milk urea nitrogen was associated with season, the higher concentration was found in the summer and autumn period, while significantly lower concentration was found in the winter and spring period. Milk urea nitrogen was the lowest in first lactation (27.34 mg/dL) and significantly increased with parities. The highest milk urea nitrogen concentration was recorded during mid-lactation stage (100-200 days), while the lowest concentration was found during late lactation stage (>200 days). Daily milk yield increased notably until above 35.00 mg/dL concentration of milk urea nitrogen, and above that level daily milk yield decreased. Milk fat and protein, content and somatic cell count had negative relationship with milk urea nitrogen concentration. The highest value of milk protein (3.41 %) was recorded when milk urea nitrogen ranged from 15 to 25 mg/dL, while milk fat percentage was the highest (4.06 %) when milk urea nitrogen ranged from 15 to 20 mg/dL. Cows with milk urea nitrogen concentration <15 mg/dL had the highest mean somatic cell count (333x103/mL). Results of this study show significant influence of analyzed non-nutritional factors on milk urea nitrogen concentration. These results may be useful in improving the accuracy of models for controlling protein-energy balance in Holstein dairy cows.